Sudden crash or long torture: The timing of market reactions to operational loss events - Biell, Lis; Muller, Aline (Journal of Banking & Finance, 2013)
An emerging literature investigating market responses to operational loss announcements concludes that financial markets tend usually to overreact to loss events. This overreaction is commonly interpreted as reputational damage. We revisit this issue by focusing on the timing of markets’ reactions and highlight two variables: the start and the speed of stock markets’ responses. It appears that when operational losses are caused by internal fraud the negative market reaction materializes earlier and faster. Industry sectors and prevailing market conditions influence the timing of market reactions as well. Our empirical findings reveal moreover that a higher initial grading of the company is associated with a later stock market reaction to the announcement. While the relative magnitude and the length of markets’ overreactions is positively correlated to the concomitant downgrading our study shows that overreaction magnitudes are also strongly correlated to our estimate of the total duration of the reaction.